The Crisis of the Philippine Progressive Movement: A Preliminary Investigation - Bello, Walden (Kasarinlan: Philippine Journal of Third World Studies, 2007)
Excerpt Allow me to address the question of why I am doing an investigation of the state of the progressive movement in the Philippines for the Forum. Probably the most important reason is that we here in the United States have been getting all sorts of conflicting reports on the state of the movement that it is time we ourselves actively clarified the issue by doing our own investigation. But also important is my own quest to salvage some meaning for my own activism in the progressive movement over the last two decades. Like many of you. I would hate to see those 20 years go to waste because the movement refused to take the first step necessary for it to again become a major player in Philippine politics: recognition of the fad that it is in crisis. This is a revised version of a talk given at a briefing on recent developments in the Philippines sponsored by the Forum for Philippine Altematives in San Francisco on July 29,1992. The views I will be expressing here are strictly my own and do not necessarily reflect those 0 the Forum for Philippine Alternatives. This article was first published in Philippine Altematives (August-September 1992), a US-based publication.